Enhanced Power Output from the PV with Low Input Ripple DC-DC Converter. Issue 11 (21st July 2018) - Venkatesan, Chandrasekar; Manickam, Chakkarapani; Reddy, Maddikara Jaya Bharata; Ganesan, Saravana Ilango; Chilakapati, Nagamani
Abstract: The primary objective of Maximum Power Point Tracking (MPPT) for PV systems connected to a low-voltage DC grid is to extract the maximum possible power output from the PV array. Normally high-frequency switched mode power converters are employed to track the maximum power. These converters, however, impose switching frequency voltage ripple on the PV output. This causes fluctuation around the Maximum Power Point (MPP) and results in power loss. These losses can be reduced using electrolytic capacitors, however, the electrolytic capacitors' lifespan is relatively shorter than that of a PV panel. In this paper, an interleaved boost converter is used to reduce high-frequency voltage ripple introduced on panel. Hence, smaller values of longer lifespan capacitors such as film capacitors will be sufficient to curtail the smaller ripple. Moreover, film capacitors are selected based on voltage ripple. Analysis was carried out for calculating voltage ripple imposed on PV module to select input filter more precisely. In addition, reduction in the voltage ripple is calculated quantitatively and is compared with that of a conventional boost converter. Enhanced power output from the PV panel is mathematically proven and experimentally demonstrated.